Organic Agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The International Federabon of Organic Agriculture Movements (IFOAM) unites the efforts of its members to promote organic agriculture as an ecologically and socially sound and sustainable method of food production which minimizes environmen tal...